Tujuan Pendidikan Dalam Q.S Az-Zariyat Ayat 56 - Meza Aulia Zahrah; Mifta Yuljannah Pasaribu; Reva Nur Amalya (STIKes Ibnu Sina Ajibarang, 2024)
Allah created humans with advantages over other creatures, namely reason, to carry out their purpose in life on earth, as in QS. Adz-Dzariyat verse 56 is to worship Allah SWT. because if humans do not carry out their obligations they will feel or be considered empty in heart and have no meaning in their lives. In order to be able to carry out the obligations/goals of life, humans must be educated so that they can become people who are obedient to worship. Basically, the main goal of education in Islam according to the Koran is to develop people who are aware of their main tasks while in the world so that in living life it includes carrying out the educational process. , both from students and educators, must be based solely as a form of devotion to Allah SWT. Education is a forum for humans to form and develop their minds to carry out their obligations. Forming minds is of course related to intellectual, emotional and spiritual matters. Therefore, to form humans who obey Allah SWT, various educational efforts are needed to make this happen. The aim of this research is to find out the aims of education in Q.S Az-zariat verse 56, what the aims of education are according to educational figures and the relevance of the aims of education in Q.S Azzariat verse 56 with the opinions of educational figures.